Brasses and brass rubbing. - Gittings, Clare (London Blandford Press, 1970)
Brass rubbings provide an historical record. This volume demonstrates how to make and collect brass rubbings. It also explains what one sees and learns from them. Index. 104p. B/W illustrations throughout.
Keywords: Fiction